Pengaruh Aplikasi Pupuk Organik Cair terhadap Hasil Panen Padi (Oryza sativa L.) - Heru Pranoto Simangunsong; Parmanoan Harahap; Meilinan Friska (Yayasan Perguruan Kampus, 2025)
Rice plants (Oryza sativa L.) are one of the staple foods for the Indonesian population. The increasing population demands an increase in the availability of rice. The development of the food crop sector, especially rice, is one of the key strategies in driving economic growth. Liquid organic fertilizers have several benefits, including encouraging and increasing the formation of leaf chlorophyll, thereby increasing the photosynthetic ability of plants and the absorption of nitrogen from the air, increasing plant vigor so that plants become sturdy and strong, increasing plant resistance to drought, stimulating the growth of production branches, increasing the formation of flowers and fruit buds, reducing the fall of flowers and fruit buds. The purpose of this study was to determine the effect of providing liquid organic fertilizer on rice plant production. This research was conducted from January 2023 to April 2023 in South Tapanuli Regency. The method in this study was a Non-Factorial Randomized Block Design (RAK) with 4 types of liquid organic fertilizer treatments. The results showed that liquid organic fertilizers did not affect all observation parameters, namely the number of panicles per clump, the number of grains per panicle, the wet weight of the grain and the dry weight of the grain. The best treatment was at U3.